Assistência pré-natal às gestantes com diagnóstico de sífilis segundo os enfermeiros da atenção primária à saúde - Reis, Eluana Maria Cristofaro (2022)
The purpose of the present study is to analyse the antenatal care to pregnant women seropositive for syphilis, according to nurses who work at the Primary Health Care within the Regional Health in the countryside of Sao Paulo State. To reach the proposed objective, a non-experimental delineation, transversal, descriptive correlational and quantitative approach research was conducted. The study was performed with nurses working with the antenatal care at the Primary Health Care, in 18 out of 20 areas which comprises the Regional Health Department XIV. The sample consists of 89 nurses working within the Family Health Strategy who were responsible for the first antenatal care appointment as well as the monitoring of pregnant women seropositive for syphilis. For the data collection, the elaboration and validation were in accordance with the Delphi Technique, followed by the pilot-test after approval from the Ethics in Research Committee. The data collection was performed on a non-presential basis, with the use of electronic forms (Google forms). Statistical Chi Square Test and Fisher Exact were used to verify the relationship between the variables. As a result of the descriptive analysis, it is possible to perceive that 64.0% of nurses act in Family Health Strategy in less or equal period of 5 years, 77.5% stated to perform their antenatal care to seropositive pregnant women based on local protocol, 88.8% do not conduct subsequential antenatal appointment, 96.6% perform rapid test at the first antenatal appointment and 64.0% perform during the second and third quarters of the pregnancy; 48.3% mentioned having treated the pregnant women with their partners regardless of the rapid test results; 36.0% mentioned the non-administration of benzylpenicillin at the health establishment without the presence of a physician and 30.4% do not administer benzylpenicillin to seropositive pregnant women. For the inferential analysis, it was identified various associations in regards of how nurses base their care in local protocols to seropositive pregnant women, it was perceived that 63.6% (p=0,000) performed subsequent antenatal care appointment, 56.8% (p=0.008) performed rapid test in the first appointment and during the second and third quarters of the pregnancy and 55.7% (p=0.019) administered benzylpenicillin at the health establishment even in the absence of a physician. Although the nurses’ opinion regarding the assistance to seropositive pregnant women have shown a greater participation rather than barriers, it is possible to identify some gaps in relation to the assistance offered and the existing protocols such as the non-prescription as well as non-administration of benzylpenicillin at the establishment, the absence of a subsequent appointment and the performance of rapid test only at the first appointment. It is expected that the actions highlighted in this study may contribute to improved practice and sensibility of nurses and managers respectively, by stimulating a reflexive process, the establishment of professional flows and empowerment for the antenatal care, to a humanized, resolutive assistance that contributes to the achievement of the preconized congenital syphilis cases target from World Health Organization.